Les Langues Néo-Latines (Boletín de la Societé des Langues Néo-Latines, Directora: Colette Pommier, 27, rue de la Chapelle, 75018, París, Francia), núms. 235, 236, 237, 1980-1981. - Garavito, Julián (Thesavrvs, 2023)
Reseñas de revistas.